Positive versus negative effects of urea – a fertilizer and fungicide – on a keystone detritivore Asellus aquaticus - Pennanen, Jenni (2024)
Human induced chemical pollution has caused a decrease in the water quality of freshwater ecosystems in large parts of the world. One of the main reasons for this is pollution from nitrogen fertilizers like urea. Urea is naturally occurring as a nitrogenous waste product and due to its high nitrogen content, it is widely used as a fertilizer. It is also used as a fungicide because of urea hydrolysis that turns it into toxic ammonia. Urea is non-toxic to mammals in environmentally relevant concentrations but can cause eutrophication of aquatic systems due to its high nitrogen concentration. In this study, I wanted to test if urea had positive or negative effects on a common keystone detritivore, the freshwater isopod Asellus aquaticus. I conducted a factorial 3x3 laboratory experiment and tested environmentally relevant concentrations (0, 1 mg/l and 10 mg/l) in two different pathways: direct and indirect and how those two pathways influenced their effect on isopod’s food consumption, growth, and pigmentation. Direct pathway means urea exposure through water and indirect effects through urea exposure of their diet (likely modifying the nitrogen content and microbial community in the leaves they consume). The results of my study suggest that urea effects on A. aquaticus are complex and showed significant interactions between size of the isopod and both pathways. This shows the importance of considering multiple exposure pathways in pollution studies. Urea can have significant ecological impacts, affecting nutrient cycling and food web dynamics.